THERMAL RADIATION AND CHEMICAL REACTION INFLUENCE ON MHD FLOW OF COUPLE STRESS FLUID PAST A VERTICAL PLATE - Ayorinde, Feyisayo; Olajuwon, B. I.; Sogbetun, L. O.; Iyoko, M. O.; Raji, M. T.; Fagbemiro, O.; Anyanwu, B. U. (FUDMA Journal of Sciences, 2025)
The behavior of fluids which incorporate microstructural effects like couple stresses, is of notable interest due to their relevance in various engineering, industrial, and biomedical applications. In this study, a comprehensive numerical investigation into the combined effects of thermal radiation and chemical reaction on magnetohydrodynamic (MHD) flow of a couple stress fluid past a vertical plate is presented. Through the application of similarity transformations, the governing equations are reduced to nonlinear ordinary differential equations. The transformed equations are solved using the BVP4C method in MATLAB, which is based on the Lobatto IIIa collocation technique, ensuring accurate and efficient numerical computations. The impact of the various parameters on velocity, temperature, and concentration within the boundary layer are illustrated graphically. Furthermore, numerical results for the local Nusselt number and Sherwood number are presented in tabular form to highlight the sensitivity of thermal and mass transport to these physical effects. The results reveal that an increase in the couple stress parameter significantly alters the fluid motion, reducing velocity near the plate and enhancing temperature and concentration profiles. Thermal radiation and magnetic field effects increase the temperature while reducing velocity, indicating energy retention and resistive electromagnetic forces. Chemical reaction reduce concentration due to reactant consumption, while Soret and Dufour effects display a complex interplay between thermal and concentration gradients. These findings not only provide physical insight into the flow behavior under multiple interactive influences but also offer valuable guidance for controlling heat and mass transfer in MHD systems involving complex non-Newtonian fluids.